Dampak Sertifikasi Guru terhadap Peningkatan Kualitas Pembelajaran Peserta Didik - Siswandari --; Susilaningsih -- (Jurnal Pendidikan dan Kebudayaan, 2013)
The purpose of this study is to examine the impact of teacher certification to improve the quality of teaching-learning process. In detail the objectives are described as follows: 1) assess the condition of teachers’ academic who have been certified, especially in the implementation of their pedagogical and professional competencies in the learning process, 2) attempts of teachers to maintain their certification in improve pedagogical and professional competencies, and 3) the impact of teacher certification to improving the quality of learning process in the classroom. The study that took place in Surakarta using mixed method approachby developing result of qualitative research to design the quantitative approach. Simple random sampling was used for quantitative approach while Criterion-based selection was used to draw sample for qualitative approach. Informants and samples involved in this study were 96 certified teachers, 74 teachers who have not been certified and 17 principals, and 424 students. Data collection method used in this study was in-depth interview, observation, documentation and questionnaires. Both interactive method and descriptive statistic were applied to analyze the data. The results of study show: 1) only 37% of certified teachers who deliver material clearly, the ability to use learning media and technology, the ability to follow the development of science and technology and learning innovation, also ability to do continuous professional development, need to be improved; 2) to maintain their professionalism, discussions between peer who teach same subjects is the most desirable method applied; 3) certified teachers have not shown an increase in the quality of teaching- learning process in the classroom significantly. This is partly indicated by the teacher ability to explain the material is still low, there is still a lack of ability to apply learning technologies (about 25% stated less to enough) and 20% of teachers indicated less attention to their student individually. The results of this study are expected to contribute to local governments in developing sustainable professionalism (continuing professional development) for teachers of post certification and to the central government in developing policies related to the welfare of teachers in Indonesia. ABSTRAK Tujuan penelitian ini adalah mengkaji dampak sertifikasi guru terhadap peningkatan kualitas pembelajaran. Secara lebih rinci tujuan tersebut diuraikan sebagai berikut : 1) mengkaji kondisi akademik guru yang telah mendapatkan sertifikat pendidik, khususnya implementasi kompetensi pedagogik dan profesi mereka dalam kaitannya dengan proses pembelajaran, 2) upaya guru untuk mempertahankan sertifikat pendidik yang telah dimiliki, khususnya dalam meningkatkan kompetensi pedagogik dan profesional, dan 3) dampak sertifikasi guru terhadap peningkatan kualitas pembelajaran di kelas. Penelitian yang mengambil lokasi di eks Karesidenan Surakarta ini menggunakan pendekatan mixed method dengan memanfaatkan hasil penelitian kualitatif untuk mendisain pendekatan kuantitatifnya. Teknik sampling yang digunakan adalah simple random sampling untuk pendekatan kuantitatif, sedangkan criterion-based selection digunakan pada saat melakukan penelitian kualitatif. Informan dan sampel yang terlibat dalam penelitian ini adalah 96 orang guru bersertifikasi, 74 guru yang belum bersertifikasi dan 17 kepala sekolah serta 424 siswa. Metode pengumpulan data yang digunakan dalam penelitian ini adalah wawancara mendalam (in-depth interview), observasi, dokumentasi dan kuesioner. Analisis data yang digunakan adalah analisis interaktif dan statistik deskriptif. Hasil penelitian ini menunjukkan: 1) hanya 37% dari guru bersertifikasi yang dapat menyampaikan materi dengan jelas, kemampuan pemanfaatan media dan teknologi pembelajaran, kemampuan mengikuti perkembangan iptek dan inovasi pembelajaran serta pengembangan keprofesian berkelanjutan masih perlu ditingkatkan; 2) diskusi antar sejawat yang mengampu mata pelajaran sama merupakan upaya yang paling diminati untuk mempertahankan profesionalitasnya; 3) guru bersertifikasi belum menunjukkan peningkatan kualitas pembelajaran di kelas secara signifikan. Hal ini antara lain diindikasikan oleh kemampuan menjelaskan materi yang masih kurang, masih kurangnya kemampuan memanfaatkan teknologi pembelajaran (sekitar 25% dinyatakan kurang sampai cukup) dan 20% guru berindikasi kurang memperhatikan keadaan siswa secara individual. Hasil penelitian ini diharapkan dapat memberikan kontribusi kepada pemerintah daerah dalam mengembangkan keprofesian berkelanjutan (continuing professional development), bagi para guru pasca sertifikasi dan bahan pertimbangan bagi pemerintah pusat dalam mengembangkan kebijakan yang terkait dengan kesejahteraan guru Indonesia.